Trichoderma Afroharzianum Ear Rot–A New Disease on Maize in Europe - Pfordt, Annette; Schiwek, Simon; Karlovsky, Petr; von Tiedemann, Andreas (Frontiers in Agronomy, 2020)
Trichoderma species are widespread filamentous fungi in soils, on plant roots and decaying plant residues. Due to their strong competitiveness and mycoparasitic activity against other fungi, particular strains of Trichoderma sp. are used in agriculture as biocontrol agents against plant pathogens. Commercial products based on strains of T. harzianum or T. afroharzianum have been applied to control Rhizoctonia spp., Fusarium spp., and Phytophthora spp. in various crops. In 2018, however, severe infections of Trichoderma on maize ears were recorded for the first time in a field in Southern Germany. Infected maize cobs were sampled, the fungus was isolated in pure culture and preliminarily identified microscopically as T. harzianum. After silk channel inoculation in the greenhouse, ear rot disease of high severity was observed. In addition to fungal colonization, the dry matter content in cobs was significantly reduced compared to water inoculated cobs. In 2018 and 2019, a total of 13 T. harzianum isolates from maize cobs and maize stalks were isolated and tested, for pathogenicity on maize plants in the greenhouse, compared to several reference isolates. Four isolates proved to be highly aggressive, two biocontrol isolates, Trichodex (T39), and strain T12, induced slight infection and eleven isolates were non-pathogenic. After sequencing of the translation elongation factor-1α (tef-1α) and internal transcribes spacers (ITS), the four highly aggressive isolates were reassigned to T. afroharzianum, while the commercial biocontrol isolates Trichodex (T39), and T12, as well as the other non-pathogenic strains belonged to T. harzianum, T. atroviride, or T. tomentosum. This, to our knowledge, is the first report on Trichoderma sp. as a pathogen causing ear rot disease in maize in Europe with the potential to incite significant yield losses. We therefore propose to name this disease as “Trichoderma ear rot on maize”.